О псевдосферических конгруэнциях в пространствах постоянной кривизны - Горькавый, В.А. (Видавничий дім "Академперіодика" НАН України, 2008)
Geometric Baacklund transformations of pseudo-spherical surfaces in n-dimensional spaces of constant curvature are studied. An analog of the classical theorems by Baacklund and Tenenblat–Terng is proved.